Oxygen‐Delivery Materials: Synthesis of an Open‐Cage Fullerene Derivative Suitable for Encapsulation of H2O2 and O2. Issue 43 (4th October 2018) - Li, Yanbang; Lou, Ning; Xu, Dan; Pan, Changwang; Lu, Xing; Gan, Liangbing
Abstract: An open‐cage [60]fullerene was prepared through a multiple‐step sequence based on peroxide‐mediated cage‐opening reactions. Key steps include repeated C60 ‐sensitized singlet‐oxygen oxidation of electron‐rich amino enol double bonds to form two lactone and two lactam moieties on the rim of the orifice. Single‐crystal X‐ray analysis shows that the 22‐membered orifice has an ellipsoid shape with the major axis at 6.7 Å and the minor axis at 3.5 Å. Encapsulation of H2 O2 was observed under atmospheric pressure at room temperature. Oxygen is also effectively trapped during the process. Abstract : Genie in a bottle : An open‐cage [60]fullerene was prepared through a multiple‐step sequence based on peroxide‐mediated cage‐opening reactions. There are two lactone and two lactam moieties on the rim of the 22‐membered orifice, which has an ellipse shape with the major axis at 6.7 Å and the minor axis at 3.5 Å. Efficient encapsulation of H2 O2 and O2 was achieved under atmospheric pressure at room temperature.